Analysis Of Universal Health Coverage (UHC) Coverage In Tana Toraja Regency - Resky, Nurhayati; Uly, Nilawati; Iskandar, Ishaq; Zamli, Zamli (Jurnal Kesehatan Mahardika, 2024)
Universal Health Coverage (UHC) is a type of health insurance in Indonesia that is managed by an official institution receiving direct orders from the President, known as the Health Social Security Administration Agency. Tana Toraja Regency is one of the areas where this program is implemented, providing health coverage to those without insurance. The goal of the study is to analyze the UHC program's implementation by the Tana Toraja Regency Government. The study used qualitative research methods, collected data through interviews, and conducted the research within Tana Toraja Regency. According to the interviews, the bureaucratic structure of UHC services in Tana Toraja Regency is straightforward, making patients feel comfortable with the service procedures. While there are still some obstacles in its implementation, 84.71% of the people in Tana Toraja have been registered as participants in the UHC program. Overall, Tana Toraja Regency has successfully achieved its target of providing health insurance for almost all its residents, despite some who have not been registered. This success is attributed to the commitment and hard work of the Tana Toraja Regency Government.